The composition of Algerian society between diversity and conflict - Ahmed abdelatif CHETTOUH (Social Sciences Journal, 1970)
In Algeria today the side of events occupies a big degree of tension and conflictbetween groups from one side and the political system in another side.Whereas it isnecessary to achieve unity and integration through the conversion of a pluralisticsociety to a culturally homogeneous society based on diversity and harmony as arequirement is necessary. It becomes important to look for mechanisms of thistransformation, and this what we will show in that study